ANALISIS PENGARUH SEKTOR MONETER DAN SEKTOR RIIL TERHADAP JUMLAH UANG BEREDAR DI INDONESIA (PERIODE 2005:III-2012:IV) - Muhammad Ali Asy'ari; Diah Wahyuningsih (Trunojoyo University of Madura, 2013)
The purpose of this study was to determine To analyze the effect of the monetary sector and the real sector on the money supply in Indonesia as well as to analyze the influence of the period of long-term and short-term monetary sector and the real sector on the money supply in Indonesia peride 2005: III-2012: IV.This study uses quantitative methods with time series data. The data gathering techniques with documentary research literature study were analyzed using a model error correction model (ECM).The results of this study are: (1) All the variables of the monetary sector (foreign exchange reserves, interest rate (BI Rate)) cointegrated in the long penjang on the money supply in Indonesia. While the long-term results obtained estimates that variable foreign reserves has a positive and significant relationship, while the BI Rate has a negative and significant relationship to the amount of money circulating in Indonesia. While the estimation results in the short-term foreign exchange reserves have a negative effect, while a BI Rate has a positive influence on JUB. (2) all the variables of the real sector (government expenditure and economic growth), cointegrated in the long penjang on the money supply in Indonesia. Estimates of long-term results obtained that the partial government spending and economic growth has a positive effect on the money supply. Moreover, the estimated short-term government spending have positive and negative effect on the economic growth of the money supply in Indonesia.